The not very reliable narratee in high resolution videogames: "Final Fantasy VII Remake" vs. "Final Fantasy VII" - Suárez Mouriño, Adrián (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Final Fantasy VII Remake is a reconstruction of the original published in 1997. Midgar, a ludoficcioal city that is part of the diegesis, goes from being represented with low-resolution graphics, pre-rendered scenarios and low-polygon models to high-resolution ones with scenarios and models of high polygonal load. In this article we will analyze, comparing the original video game and its remake, how this affects the narration, more specifically the reliability of the player in his role as narratee.
Keywords: storytelling in videogames; japanese videogames; Final Fantasy VII; narratee; complex fiction; cinema and videogames